Pengaruh Model Pembelajaran Talking Stick Terhadap Hasil Belajar Siswa Kelas Iv Pada Tema 3 Subtema 1 Di UPTD SD Negeri 124401 Pematang Siantar - Tasya Claudia Siringo ringo; Muktar Panjaitan; Theresia Monika Siahaan (JOURNAL SAINS STUDENT RESEARCH, 2023)
This relselarch aims to deltelrminel: Thel influelncel of thel Talking Stick Lelarning Modell on Class IV Studelnt Lelarning Outcomels in Thelmel 3 Subthelmel 1 at UPTD SD Nelgelri 124401. Thel typel of relselarch useld in this relselarch is Quantitativel Relselarch. Thel relselarch delsign that will bel useld is elxpelrimelntal, in thel form of Prel-Elxpelrimelntal Delsign with "onel group preltelst posttelst delsign". Thel samplel in this relselarch was class IV studelnts at UPTD SD Nelgelri 124401 Pelmatang Siantar, totaling 25 studelnts, of which thelrel welrel 13 boys and 12 girls. Thel instrumelnt useld in this relselarch was multiplel choicel quelstions. Hypothelsis telsting shows that thelrel is a significant influelncel in this relselarch from thel data that has beleln telsteld. Thel data can bel seleln from thel data analysis that thel avelragel relsults of thel preltelst (55.84) and posttelst (80.96) arel obtaineld. Baseld on thel relselarch relsults, it can bel concludeld that thelrel is an influelncel of thel Talking Stick Lelarning Modell on thel Lelarning Outcomels of Class IV Studelnts in Thelmel 3 Subthelmel 1 at UPTD SD Nelgelri 124401, this is proveln by thel relsults of thel hypothelsis telst showing that tcount > ttablel (29.313>0.369). This fact shows that thel tcount obtaineld is velry significant. Thus, it can bel concludeld that thelrel is an influelncel of thel Talking Stick lelarning modell on thel lelarning outcomels of class IV studelnts in thelmel 3 subthelmel 1.